Bio-adsorbents from banana peel and corncob in reducing Naphthol Yellow S dye - Eri, Iva Rustanti; Marlik, Marlik; Khambali, Khambali (International Journal of Advances in Applied Sciences, 2025)
Naphthol Yellow S, a textile dye waste, poses environmental pollution due to its degradable chromophore and auxochrome groups, necessitating processing. The aim was to analyze the adsorption kinetics of banana peel and corncob bioadsorbents to reduce the dye Naphthol Yellow S in wastewater. This research was a true experiment and the object used was an artificial Naphthol Yellow S solution with an initial concentration of 80 ppm applied to the adsorbent mass of 0.1, 0.2, and 0.3 grams and contact time of 3, 6, 9, and 12 hours. Dye levels were measured before and after treatment using a spectrophotometer. The best adsorption test occurred on the banana peel bioadsorbent with an adsorbent mass of 0.3 grams and a stirring time of 3 hours. The adsorption study of banana peel and corncob bioadsorbents showed that the entire adsorption process of Naphthol Yellow S dye followed the Langmuir isothermal adsorption model with R2 coefficients of 0.9953 and 0.999, respectively, and maximum adsorption capacities of 4.6516 and 5.2825 mg/g, respectively. The activated carbon adsorption kinetics followed the second order, with R2 values of 0.9737 and 0.9152, respectively. This study concluded that the bioadsorbent of banana peels and corncob was able to reduce the dye Naphthol Yellow S.